Jenis-Jenis Cacing Parasit Saluran Pencernaan pada Hamster Syria Mesocricetus auratus (Waterhause, 1839) di Kota Padang - Riski Andrian Jasmi; - Mairawita; - Dahelmi (Universitas Andalas, 2014)
A study about gastrointestinal helminths of Mesocricetus auratus (Waterhause, 1839) in Padang, West Sumatera was conducted from March to July 2013. This study was aimed to identify species of gastrointestinal helminths and to determine the prevalence of gastrointestinal helminths of M. auratus in Padang. Sampling was conducted by using Purposive methods. Those samples were examined by using direct observation, floating-centrifuge and sedimentation method. A total of four helminths species that belonging to two phylums and four orders was collected. The obtained helminths were Hymenolepis nana Siebold, 1852 (Cyclophyllidea), Syphacia obvelata Rudolphi, 1802 (Ascaridida), Sp. 1 (Strongylida), and Sp. 2 (Enoplida). The prevalence of Syphacia obvelata, Hymenolepis nana, Sp. 1 and Sp. 2 were 57,1%, 50%, 17,1% and 17,1%, respectively.